Currency Exposure And Time Scales: Application Of Wavelet Method To Malaysian Non-financial Firms - Wan Nurhanan Wan Suhaimi; Hishamuddin Abdul Wahab; Rabihah Md Sum (Blue Eyes Intelligence Engineering & Sciences Publication, 2024)
International Journal of Recent Technology and Engineering (IJRTE) ISSN: 2277-3878, Volume-8 Issue-3S3, November 2019